Peran Ekstrakurikuler PAI dalam Membangun Sikap Spiritual, Moral, dan Perilaku Peserta Didik Sehari-hari - Anton, Anton; Fathoni, Ahmad; Aziz, Abdul (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This study aims to discuss the importance of Islamic Religious Education (PAI) extracurricular activities in forming students' character and social attitudes, as well as its role in overcoming promiscuity among teenagers. Wrong social interactions can affect behavior and morality, making it crucial to choose good friends in accordance with Islamic teachings. Extracurricular PAI activities outside of regular school hours play a significant role in character building, spiritual attitudes, and students' moral development through activities based on Islamic values. Despite challenges in attracting student interest, approaches such as ensuring proper timing, raising awareness about the importance of religious education, and providing adequate facilities can enhance student participation. PAI extracurriculars also help students develop social attitudes, leadership, empathy, and responsibility. These activities include Islamic leadership training, religious study sessions, social service, and moral guidance, all aiming to form students' characters that are caring, disciplined, and responsible.